2002
DOI: 10.1128/mcb.22.24.8580-8591.2002
|View full text |Cite
|
Sign up to set email alerts
|

Essential, Nonredundant Role for the Phosphoinositide 3-Kinase p110δ in Signaling by the B-Cell Receptor Complex

Abstract: Many receptor and nonreceptor tyrosine kinases activate phosphoinositide 3-kinases (PI3Ks). To assess the role of the ␦ isoform of the p110 catalytic subunit of PI3Ks, we derived enzyme-deficient mice. The mice are viable but have decreased numbers of mature B cells, a block in pro-B-cell differentiation, and a B1 B-cell deficiency. Both immunoglobulin M receptor-induced Ca 2؉ flux and proliferation in response to B-cell mitogens are attenuated. Immunoglobulin levels are decreased substantially. The ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
283
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(298 citation statements)
references
References 39 publications
10
283
4
1
Order By: Relevance
“…In addition, knockouts of some of the regulatory molecules directly involved in the regulation of the mechanistic components of cell migration have been described and are listed separately in the table. Knockouts of other regulatory molecules, such as PI3K and PTEN, have also been characterized (Di Cristofano et al, 1998;Jou et al, 2002;Katso et al, 2001;Stambolic et al, 2000;Suzuki et al, 2003), but are too general to be implicated directly in migration and have therefore been removed from our list.…”
Section: Migration-dependent Developmental Defects Key Cell Migrationmentioning
confidence: 99%
“…In addition, knockouts of some of the regulatory molecules directly involved in the regulation of the mechanistic components of cell migration have been described and are listed separately in the table. Knockouts of other regulatory molecules, such as PI3K and PTEN, have also been characterized (Di Cristofano et al, 1998;Jou et al, 2002;Katso et al, 2001;Stambolic et al, 2000;Suzuki et al, 2003), but are too general to be implicated directly in migration and have therefore been removed from our list.…”
Section: Migration-dependent Developmental Defects Key Cell Migrationmentioning
confidence: 99%
“…Similar results were observed using LY294002 inhibitor (data not shown). Because the PI3K catalytic subunit p110␦ contributes a significant proportion of PI3K signaling in B cells (31)(32)(33), we examined the role of this isoform, using the p110␦-selective inhibitor IC (37,38) and B cells from mice carrying an inactivating mutation of p110␦ (33). Pretreatment of normal B cells with IC partially inhibited their ability to induce IL-2 production in a dose-dependent fashion (Fig.…”
Section: The P110␦ Signaling Is Required For Bcr-mediated Ag Presentamentioning
confidence: 99%
“…30). The expression of the p110␦ isoform is restricted to immune cells and has been shown to play critical roles in B cell activation (31)(32)(33). In this study, we have investigated whether p110␦ plays a role in Ag presentation function of primary B cells using both genetic inactivation of p110␦ and a p110␦-specific inhibitor IC87114 (IC).…”
mentioning
confidence: 99%
“…Our previous study found that T cells from p110d-D910A mice had reduced antigen-induced proliferation in vitro, but this appears in some cases to be overcome by strong signaling through costimulatory receptors [11]. In contrast, p110d-deficient B cells have major defects in activation by multiple stimuli in vitro, and blunted antibody responses in vivo [11][12][13]. Thus, while PI3K isoforms likely play distinct roles in B cells, T cells and neutrophils, their respective roles in regulating systemic cytokine production patterns, cell-mediated immunity and host defense functions remain unexplored.…”
Section: Introductionmentioning
confidence: 99%